Complementary alternative medicine use among postpartum mothers in a primary care setting: a cross-sectional study in Malaysia - Nik Farah Nik Yusof Fuad; Siew Mooi Ching; Dayangku Hayaty Awg Dzulkarnain; Ai Theng Cheong; Zainul Amiruddin Zakaria (BMC, 2020)
Abstract Background Complementary alternative medicine (CAM) is widely used among postpartum mothers to maintain their well-being. This study aims to determine the prevalence and factors associated with CAM use among postpartum mothers in a primary-care clinic in Malaysia. Methods This is a cross-sectional study of 725 postpartum mothers, aged 18 and above, attending a primary-care clinic. The systematic sampling method was used to recruit patients through a structured, self-administered questionnaire. Data analysis was conducted using SPSS version 23. Multiple logistic regression was used to identify the predictors of CAM use among postpartum mothers. Results The prevalence of CAM use among postpartum mothers was 85.5%. Manipulative body therapies, including massage, reflexology, hot stone compression and body wrapping were the most widely used methods of CAM (84.1%) among postpartum mothers, followed by biological-based therapies (33.1%). More than half of the respondents (52.1%) opted to use CAM, as they had observed good results from other CAM users. However, our study showed that 57.1% of mothers who consumed herbal medicine reported neonatal jaundice in their newborn. The median of the expenditure on CAM usage was 250 Malaysian Ringgits, or USD 61.3 per month. According to multiple logistic regression analyses, being Muslim (OR = 5.258, 95% CI: 2.952-9.368), being Malay (OR = 4.414, 95% CI: 1.18-16.56), having a higher educational level (OR = 2.561, 95% CI: 1.587-4.133) and having delivered via spontaneous vaginal delivery (OR: 5.660, 95% CI: 3.454-9.276) had a significantly positive association with CAM use among postpartum mothers. Conclusions The prevalence of CAM use was high (8 out of 10) among postpartum mothers. Postpartum mothers who are Malay, Muslim, have a higher educational level and who have had spontaneous vaginal delivery tended to use CAM more. Manipulative body therapies, including massage, reflexology, hot stone compression and body wrapping, were the most widely used forms of CAM, followed by biological-based therapies. More than half of the mothers who consumed herbal medicine reported neonatal jaundice in their newborn. Thus, education to increase awareness regarding the consumption of herbs is urgently required in this country.